AFRICAN AMERICANS ARE LESS LIKELY THAN CAUCASIANS TO TAKE ANTITHROMBOTIC MEDICATION A YEAR AFTER STROKE. (11th November 2018) - Sheehan, O; Dhamoon, M; Bettger, J; Huang, J; Rhodes, J; Roth, D
Abstract: Recurrent strokes are common. Secondary prevention guidelines recommend medication regimens including antithrombotic, lipid lowering and antihypertensive medications as appropriate to reduce recurrent stroke risk. The stroke population has high rates of multimorbidity and patients often struggle to integrate these new prescriptions into their medication regimens. We examined the effects of race and gender on baseline prescription and maintenance of secondary prevention regimens in the Caring for Adults Recovering from the Effects of Stroke (CARES) study, an ancillary study of the national REasons for Geographic and Racial Differences in Stroke (REGARDS). Ischemic stroke survivors (N = 181; 37% African American) with family caregivers had medications recorded at hospital discharge and an average 12.7 months later during a home visit when the medications they were actually taking were reviewed in person. At discharge, antithrombotic prescription (94.4%), lipid lowering medications (77.7%) and antihypertensives (88.3%) were common and there were no race or gender effects in discharge prescription rates. One year later, maintenance of initially prescribed medication had fallen to 86.0% for antithrombotics (p=0.003) and 68.2% for lipid lowering (p=0.005) but increased to 92.8% for antihypertensives (p=0.12). African Americans were more likely to have stopped antithrombotics than Caucasians (18.8% v 7.6%, p=0.03). Women were also more likely than men to stop their antithrombotics (p=0.07). Many factors can contribute to stopping medications including patient choice, side effects, or physician recommendations. The effect of changes in patterns of medication usage including reduced use of antithrombotics and increased use of antihypertensives on health outcomes deserves continued investigation.